Theatre Comique at 14 Tremont Row, 1916 - Dadmun Company (Tufts Archival Research Center, 2005)
Elevated view southwest of 14 Tremont Row, located between Howard Street to the northwest and Scollay Square to the southeast. Signage, light fixtures and motion picture posters adorn the facade of the building, which faces northeast. 9 x 5 7/8, 10 x 7 3/4 overall Photographs